Harm to Others from Substance Use and Abuse: The Underused Potential in Nationwide Registers - Ingunn Olea Lund; Anne Bukten (SAGE Publishing, 2015)
This article considers the potential in using nationwide registers to study harm to others from substance use and abuse. The advantages of using registry data include the opportunity to include the data on the entire population nationwide and continuously updated longitudinal datasets; they allow for studying small subpopulations and have little missing data. Personal identification numbers and family numbers enable linkage of data from different registers. Such datasets can include extensive information on individual and family levels. In this article, we provide an introduction to nationwide registers and explain how they can be applied to investigate two types of third-party harms: harm to children and harm to partners/spouses from substance use and abuse in parents and partners/spouses. Finally, we discuss challenges, benefits, and ethical considerations regarding the use of such data.